Molecular identification of Candida species isolated from cases of neonatal candidemia using polymerase chain reaction-restriction fragment length polymorphism in a tertiary care hospital - Akeela Fatima; Gulnaz Bashir; Tehmeena Wani; Abiroo Jan; Amrish Kohli; Mosin S Khan (Wolters Kluwer Medknow Publications, 2017)
Context: Candida spp. is an emerging cause of bloodstream infections worldwide. Delay in speciation of Candida isolates by conventional methods and resistance to antifungal drugs in various Candida species are responsible for the increase in morbidity and mortality due to candidemia. Hence, the rapid identification of Candida isolates is very important for the proper management of patients with candidemia. Aims: The aim was to re-evaluate the identification of various Candida spp. by polymerase chain reaction (PCR)-restriction fragment length polymorphism (RFLP) and to evaluate the accuracy, speed, and cost of phenotypic methodology versus PCR-RFLP. Settings and Design: Hospital-based cross-sectional study. Materials and Methods: Ninety consecutive clinical isolates of seven Candida species, isolated from blood of neonates and identified by routine phenotypic methods, were re-evaluated using universal primers internal transcribed spacer 1 (ITS1) and ITS4 for PCR amplification and Msp I restriction enzyme for RFLP. Statistical Analysis Used: Kappa test for agreement. Results: The results of PCR-RFLP were 100% in agreement with those obtained using conventional phenotypic methods. Identification could be achieved within 3 work days by both the methods. Our routine methods proved to be cost effective than PCR-RFLP. Conclusions: We can continue with our routine phenotypic methods and PCR-RFLP can be used for periodic quality control or when conventional methods fail to identify a species.